ASIAN INTEGRATION AND FOREIGN WORKERS MOBILITY - Mukiwihando, Rynalto (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
This paper aims to obtain empirical insight of the factors promoting foreign workers mobility in Asian integration, particularly within ASEAN plus Three countries. Using questionnaire as a qualitative research tool, this study tries to capture general perspective of Asian integration and common market idea as being implemented in European case. Motivation of this study is to provide a preliminary picture whether workers will start to another country if Asian integration start soon and what are the affectig factors. All of the finding results are consistent with several previous studies Study results demonstrate that almost all of respondents believe that foreign workers mobility is affected in Asian Integration by more job opportunity supplies. The most important factors in both foreign workers inflow and outflow is technology spillover Moreover, most respondents also agree that all foreign workers are being treated equally or even higher in some cases, compare to other local workers